Intussusceptions in Adults: A Retrospective Interventional Series of Cases - Gupta, Rakesh Kr; Agrawal, Chandra Shekhar; Yadav, Rohit; Bajracharya, Amir; Sah, Panna Lal (Health Renaissance, 2011)
Background: Intussusception is a different entity in adults than it is in children and is usually secondary to a definable pathology. Objective: To review adult intussusception: clinical features, diagnosis and their management. Subjects and methods: A retrospective review of 38 cases of intussusception in individuals older than 18 years of age presenting to BPKIHS Dharan, Nepal from January 2003 to December 2009 was done. Results: In six years, there were thirty-eight patients of surgically proven adult intussusception. The patients. mean age was 49.6 ± 16.2 years, M: F ratio was 1.3:1. Intestinal obstructions of various extents were the commonest presentation in twenty-seven patients (71%). There were 42% enteric, 32% ileocolic and 26% colonic AI. The diagnostic accuracy of the ultrasonography was 78.5%, CT scan was 90% and colonoscopy was 100%. The pathological lesions were found in 94% of AI. Among the pathological lesion, enteric have 62% benign, 38% malignant, ileocolic have 50% benign, 50% malignant, and in colocolic 70% malignant, 30% benign. In enteric AI, 68% were reduced successfully, 25% reduction was not attempted. Of ileocolic AI, 58.3% were reduced successfully, 41.6% had resection without reduction. Of colocolic AI, 30% of them were reduced successfully before resection, 70% had resection without reduction. Conclusion: CT scanning is the most useful diagnostic radiologic method in AI. Colonoscopy is the most accurate in ileocolic and colonic AI. Small-bowel intussusception should be reduced before resection if the underlying etiology is suspected to be benign or if the resection required without reduction is deemed to be massive. Large bowel should generally be resected without reduction because pathology is mostly malignant. Keywords: Adult intussusception (AI); Bowel obstruction; CT scan DOI: 10.3126/hren.v8i3.4208 Health Renaissance, September-December 2010; Vol 8 (No.3);158-165